Analisis implemtasi kurikulum merdeka dalam capaian kompetensi pembelajaran PJOK melalui model CIPP (literature review) - Karno Dinata; I Wayan Lasmawan; I Gusti Putu Suharta; Muhammad Wahyu Aby Putra; Muhammad Danil Rizky; Muhammad Khairil Umam; Muhammad Zainul Firdaus; Nizaril Fatahar; Regi Santa Laksana; Riski Aulia; Rizal Wahyu Putra (Universitas Hamzanwadi, 2023)
The purpose of the study was to analyze the implementation of the independent curriculum in the achievement of PJOK learning competencies. This type of qualitative descriptive research through a literature study approach (literature review). Data collection techniques by collecting various sources of journals, articles and books through publish or perish applications and goggle scoler. From the data collected, it is then analyzed, studied to be interpreted and described in detail, then described in the scope of the discussion. The results of the analysis that the implementation of the independent curriculum in the learning outcomes of PJOK through the evaluation of the CIPP model from the context aspect includes determining policies, needs and objectives for increasing PJOK knowledge and skills to be fundamental to achieving competence, input aspects include the preparation of strategies, procedures, approaches in the main learning process in knowing the achievement of PJOK learning competencies, process aspects include planning, implementation and evaluation, product aspects refer to the results of learning outcomes in accordance with the minimum completion criteria. It is concluded that the formation of talent and interest in sports achievement as an evaluation of a system includes context evaluation, input evaluation, process evaluation and product evaluation